Characterization of steel reinforcement corrosion in concrete using 3D laser scanning techniques. (8th February 2021) - Zhang, Junzhi; Huang, Jin; Fu, Chuanqing; Huang, Le; Ye, Hailong
Highlights: Cross-sectional area distribution of non-uniform corroded steel bars varies with increasing corrosion rate. Relative yield strength decreases linearly and relative ultimate elongation decreases exponentially. Little effect of corrosion on the yield strength and ultimate strength of the steel bars. Non-uniform corroded steel bars have shorter necking length and tend to brittle failure. Abstract: In this work, to investigate the characteristics of non-uniform corrosion of steel bars more accurately, a new experimental method was proposed, which can rapidly generate non-uniformly distributed rust around steel bars in concrete. The precise average and critical cross-sectional area along the longitudinal direction of corroded steel bars were then obtained using the three-dimensional (3D) laser scanning. Based on critical section loss rate, the effects of non-uniform corrosion on the degradation of mechanical properties of steel bars were studied. The corrosion morphology, mechanical properties, and tensile failure patterns of uniformly and non-uniformly corroded steel bars were compared and elaborated.